Jigger Persistence and Associated Factors among Households in Mayuge District, Uganda - Namuhani, Noel; Kiwanuka, Suzanne N. (International Journal of Health Sciences and Research (IJHSR), 2016)
Jigger infestation has serious health consequences and has been associated with considerable morbidity and difficulties in walking or using the hands, which prevent the victims from leading productive life. Persistent jigger infestation produces even more dire outcomes such as disability and mortality due to secondary infections. In Uganda, jigger infestation has been reported to be at epidemic levels and has persisted especially in the rural communities of the country, some households being at a higher risk of Persistent Jigger Infestation than others. This study aimed at assessing factors associated with persistent jigger infestation among households of Mayuge district, Uganda. Methods: A total of 296 households in Bukatube Sub County, Mayuge district, were randomly selected to participate in the study. Persistent Jigger infestation was defined as individuals who experienced at least four jigger re- infestations within the past 30 days. Semi structured questionnaires, observational checklists and key informant interview guides were used to collect data. Data was analyzed using Epi info version 3.5.1, descriptive statistics were obtained, bi variable and multivariable analysis was done, to examine the association between the different variables. Results: The prevalence of jigger infestation was found to be 25.0%, but of these, 58.3% had persistent jigger infestation. Factors that increased the likely hood of persistent jigger infestation included; low monthly income (AOR 2.84 95%CI 1.04-7.75), littered compound (AOR 5.18, 95%CI 2.56-10.46), earthen floor (AOR 3.38 95%1.08-10.55), and cracked walls (AOR 4.63 95%CI 2.23-9.60). Individuals who were knowledgeable about jigger prevention had reduced chances of being persistently infested with jiggers (AOR 0.47 95%CI 0.25-0.90). Conclusion: The prevalence of jigger infestation and the level of persistence were moderately high. There is need to increase awareness of community members on how to control jiggers and appropriate measures to address the nature of houses that people live in, need to be implemented.
Keywords: Jigger infestation; Persistent jigger infestation; ecto parasitic infection